2023
DOI: 10.1186/s12884-023-05664-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of midwifery-led care on pregnancy outcomes in low- and middle-income countries: a systematic review and meta-analysis

Abstract: Background Midwifery-led care is an evidence-based practice in which a qualified midwife provides comprehensive care for low-risk pregnant women and new-borns throughout pregnancy, birth, and the postnatal period. Evidence indicates that midwifery-led care has positive impacts on various outcomes, which include preventing preterm births, reducing the need for interventions, and improving clinical outcomes. This is, however, mainly based on studies from high-income countries. Therefore, this sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Estos desafíos han centrado sus estándares en garantizar la satisfacción de las personas, incorporando tópicos de interculturalidad, género y ética en la prestación de servicios [39], más allá de la estructura curricular, recursos e infraestructura y de otros aspectos relevantes para la calidad educativa. En contraste, en países de ingresos bajos y medios que se encuentran en etapas tempranas de transición, donde los sistemas de acreditación aún no están plenamente establecidos o no son específicos para partería, la formación profesional continúa centrada en la reducción de la mortalidad materna y neonatal [4,13,75]. En estos, la satisfacción de las personas aún no se ha integrado como un elemento fundamental en los procesos de acreditación, ya que los recursos, infraestructura y los aspectos curriculares asociados a la formación de competencias profesionales para abordar indicadores básicos maternos y perinatales, son los priorizados en los estándares de acreditación [36].…”
Section: Discussionunclassified
“…Estos desafíos han centrado sus estándares en garantizar la satisfacción de las personas, incorporando tópicos de interculturalidad, género y ética en la prestación de servicios [39], más allá de la estructura curricular, recursos e infraestructura y de otros aspectos relevantes para la calidad educativa. En contraste, en países de ingresos bajos y medios que se encuentran en etapas tempranas de transición, donde los sistemas de acreditación aún no están plenamente establecidos o no son específicos para partería, la formación profesional continúa centrada en la reducción de la mortalidad materna y neonatal [4,13,75]. En estos, la satisfacción de las personas aún no se ha integrado como un elemento fundamental en los procesos de acreditación, ya que los recursos, infraestructura y los aspectos curriculares asociados a la formación de competencias profesionales para abordar indicadores básicos maternos y perinatales, son los priorizados en los estándares de acreditación [36].…”
Section: Discussionunclassified
“…These studies have demonstrated that patient satisfaction with care and outcomes does not significantly differ between midwife-led care and the other care group [ 31 ]. Moreover, in certain instances, care provided by midwives has been associated with a higher satisfaction with care and improved outcomes [ 32 , 33 , 34 , 35 ]. Despite the wealth of research on midwifery care during birth and the postnatal period, the focus on antenatal care has been comparatively scarce [ 36 ].…”
Section: Discussionmentioning
confidence: 99%